Step
*
2
of Lemma
unsat-omega_step
1. n : ℕ
2. eqs : {L:ℤ List| ||L|| = (n + 1) ∈ ℤ}  List
3. ineqs : {L:ℤ List| ||L|| = (n + 1) ∈ ℤ}  List
4. ¬if eqs = Ax then if ineqs = Ax then 0 otherwise ||hd(ineqs)|| - 1 otherwise ||hd(eqs)|| - 1 < 1
5. ¬(n = 0 ∈ ℤ)
6. xs : ℤ List
7. x1 : (∀as∈eqs.xs ⋅ as =0)
8. x2 : (∀bs∈ineqs.xs ⋅ bs ≥0)
9. first-success(λL.find-exact-eq-constraint(L);eqs) ∈ i:ℕ||eqs||
   × x:{x:ℤ List| x = eqs[i] ∈ (ℤ List)} 
   × {i@0:ℕ+||eqs[i]||| |eqs[i][i@0]| = 1 ∈ ℤ} ?
10. y : 0 = 0 ∈ ℤ
11. first-success(λL.find-exact-eq-constraint(L);eqs)
= (inr Ax )
∈ (i:ℕ||eqs|| × x:{x:ℤ List| x = eqs[i] ∈ (ℤ List)}  × {i@0:ℕ+||eqs[i]||| |eqs[i][i@0]| = 1 ∈ ℤ} ?)
⊢ unsat(if null(eqs)
then case gcd-reduce-ineq-constraints([];shadow_inequalities(ineqs)) of inl(ineqs') => inl <[], ineqs'> | inr(x) => inr \000Cx 
else inl <[], (eager-map(λeq.eager-map(λx.(-x);eq);eqs) @ eqs) @ ineqs>
fi )
⇒ False
BY
{ xxx(BoolCase ⌜null(eqs)⌝⋅ THENA Auto)xxx }
1
1. n : ℕ
2. eqs : {L:ℤ List| ||L|| = (n + 1) ∈ ℤ}  List
3. ineqs : {L:ℤ List| ||L|| = (n + 1) ∈ ℤ}  List
4. ¬if eqs = Ax then if ineqs = Ax then 0 otherwise ||hd(ineqs)|| - 1 otherwise ||hd(eqs)|| - 1 < 1
5. ¬(n = 0 ∈ ℤ)
6. xs : ℤ List
7. x1 : (∀as∈eqs.xs ⋅ as =0)
8. x2 : (∀bs∈ineqs.xs ⋅ bs ≥0)
9. first-success(λL.find-exact-eq-constraint(L);eqs) ∈ i:ℕ||eqs||
   × x:{x:ℤ List| x = eqs[i] ∈ (ℤ List)} 
   × {i@0:ℕ+||eqs[i]||| |eqs[i][i@0]| = 1 ∈ ℤ} ?
10. y : 0 = 0 ∈ ℤ
11. first-success(λL.find-exact-eq-constraint(L);eqs)
= (inr Ax )
∈ (i:ℕ||eqs|| × x:{x:ℤ List| x = eqs[i] ∈ (ℤ List)}  × {i@0:ℕ+||eqs[i]||| |eqs[i][i@0]| = 1 ∈ ℤ} ?)
12. eqs = [] ∈ ({L:ℤ List| ||L|| = (n + 1) ∈ ℤ}  List)
⊢ unsat(case gcd-reduce-ineq-constraints([];shadow_inequalities(ineqs))
 of inl(ineqs') =>
 inl <[], ineqs'>
 | inr(x) =>
 inr x )
⇒ False
2
1. n : ℕ
2. eqs : {L:ℤ List| ||L|| = (n + 1) ∈ ℤ}  List
3. ¬(eqs = [] ∈ ({L:ℤ List| ||L|| = (n + 1) ∈ ℤ}  List))
4. ineqs : {L:ℤ List| ||L|| = (n + 1) ∈ ℤ}  List
5. ¬if eqs = Ax then if ineqs = Ax then 0 otherwise ||hd(ineqs)|| - 1 otherwise ||hd(eqs)|| - 1 < 1
6. ¬(n = 0 ∈ ℤ)
7. xs : ℤ List
8. x1 : (∀as∈eqs.xs ⋅ as =0)
9. x2 : (∀bs∈ineqs.xs ⋅ bs ≥0)
10. first-success(λL.find-exact-eq-constraint(L);eqs) ∈ i:ℕ||eqs||
    × x:{x:ℤ List| x = eqs[i] ∈ (ℤ List)} 
    × {i@0:ℕ+||eqs[i]||| |eqs[i][i@0]| = 1 ∈ ℤ} ?
11. y : 0 = 0 ∈ ℤ
12. first-success(λL.find-exact-eq-constraint(L);eqs)
= (inr Ax )
∈ (i:ℕ||eqs|| × x:{x:ℤ List| x = eqs[i] ∈ (ℤ List)}  × {i@0:ℕ+||eqs[i]||| |eqs[i][i@0]| = 1 ∈ ℤ} ?)
⊢ unsat(inl <[], (eager-map(λeq.eager-map(λx.(-x);eq);eqs) @ eqs) @ ineqs>) 
⇒ False
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  eqs  :  \{L:\mBbbZ{}  List|  ||L||  =  (n  +  1)\}    List
3.  ineqs  :  \{L:\mBbbZ{}  List|  ||L||  =  (n  +  1)\}    List
4.  \mneg{}if  eqs  =  Ax  then  if  ineqs  =  Ax  then  0  otherwise  ||hd(ineqs)||  -  1  otherwise  ||hd(eqs)||  -  1  <  1
5.  \mneg{}(n  =  0)
6.  xs  :  \mBbbZ{}  List
7.  x1  :  (\mforall{}as\mmember{}eqs.xs  \mcdot{}  as  =0)
8.  x2  :  (\mforall{}bs\mmember{}ineqs.xs  \mcdot{}  bs  \mgeq{}0)
9.  first-success(\mlambda{}L.find-exact-eq-constraint(L);eqs)  \mmember{}  i:\mBbbN{}||eqs||
      \mtimes{}  x:\{x:\mBbbZ{}  List|  x  =  eqs[i]\} 
      \mtimes{}  \{i@0:\mBbbN{}\msupplus{}||eqs[i]|||  |eqs[i][i@0]|  =  1\}  ?
10.  y  :  0  =  0
11.  first-success(\mlambda{}L.find-exact-eq-constraint(L);eqs)  =  (inr  Ax  )
\mvdash{}  unsat(if  null(eqs)
then  case  gcd-reduce-ineq-constraints([];shadow\_inequalities(ineqs))
            of  inl(ineqs')  =>
            inl  <[],  ineqs'>
            |  inr(x)  =>
            inr  x 
else  inl  <[],  (eager-map(\mlambda{}eq.eager-map(\mlambda{}x.(-x);eq);eqs)  @  eqs)  @  ineqs>
fi  )
{}\mRightarrow{}  False
By
Latex:
xxx(BoolCase  \mkleeneopen{}null(eqs)\mkleeneclose{}\mcdot{}  THENA  Auto)xxx
Home
Index